2002
DOI: 10.1108/10650750210430150
|View full text |Cite
|
Sign up to set email alerts
|

XML and global name access control

Abstract: This paper discusses why the MARC21-based authority format has failed in a global setting and details the use of XML and its related technologies to achieve global name access control.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2005
2005
2015
2015

Publication Types

Select...
2
2
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 0 publications
0
6
0
Order By: Relevance
“…More work is needed to study the process of extending existing authority files based on historical reference works, merging controlled vocabularies from multiple sources, and finally incorporating local authority files into general authority files as it seems appropriate. Our experience suggests that a distributed model of authority control as suggested by several researchers [20,17,31] could provide a standardized infrastructure for this process.…”
Section: Named Entitiesmentioning
confidence: 98%
“…More work is needed to study the process of extending existing authority files based on historical reference works, merging controlled vocabularies from multiple sources, and finally incorporating local authority files into general authority files as it seems appropriate. Our experience suggests that a distributed model of authority control as suggested by several researchers [20,17,31] could provide a standardized infrastructure for this process.…”
Section: Named Entitiesmentioning
confidence: 98%
“…Can express a Romanization scheme As previously suggested (Lam, 2002;Smith, 1990), displaying the Romanization scheme would assist the user. FRAD has an attribute "transliteration scheme," which is…”
Section: Can Differentiate Transliteration and Transcriptionmentioning
confidence: 99%
“…Following a debate, the HKCAN decided to use field 1XX for LCNAF headings and 7XX for Chinese scripts ( Joint University Librarians Advisory Committee, 2010). Lam (2002) also reviewed the two MARC21/A models and reported that, while Model A allows better linkage between vernacular scripts and their transliterations than Model B, it is not eagerly supported by library vendors and bibliographic utilities. Thus, neither model is suitable for global distribution.…”
mentioning
confidence: 99%
“…In 2002, the HKUST Library began the development of an XML Name Access Control Repository [4] to address the problems experienced by catalogers and catalog users in identifying personal authors whose names are in non-Latin scripts [5].…”
Section: Global Name Access Controlmentioning
confidence: 99%